The Challenges of Early Initiation of Breastfeeding in Post Sectio Caesarea Patients - Anita; Lia Lajuna; Nurlaili Ramli (Science Midwifery, 2022)
The implementation of initiation of breastfeeding has physiological benefits to help the contraction of the mother's uterus and provide benefits for the survival of the baby. Success and failure in the implementation of initiation of breastfeeding is influenced by many challenges. This systematic review aims to analyze the challenges of implementing Early Breastfeeding Initiation (IMD) in post-SC patients. This study is a systematic review using online databases, namely Scholar, ScienceDirect, ProQuest, and EBSCO. The keywords used are Early Initiation of Breastfeeding, Post Sectio Caesarea, Patients.. The selection process used the PRISMA protocol so that 15 articles were obtained that met the inclusion criteria. The findings of the review indicated that there are still challenges to early initiation of breastfeeding, such as the development of dedicated health workers, lack of training for early initiation of breastfeeding after implementing SC, discomfort, little support from health workers, and delayed breastfeeding provided by influencers Practice room and advice on infant formula and infant formula from health workers.